Meta-analisis penggunaan LKS inkuiri terbimbing dalam pembelajaran fisika - Desra Yarsina; Silvi Yulia Sari; Yenni Darvina; Asrizal Asrizal (Universitas Negeri Padang, 2020)
This study aims to analyze the effectiveness of Guided Inquiry Worksheets in Physics Learning. The method used was a meta-analysis that summarizes and analyzes research results that have been published nationally and internationally relating to the guided inquiry student worksheet towards learning Physics. The analysis sample was twenty journals published in the 2013-2020 range. Writing instruments in the form of coding sheets that summarize data and journal information. The results of this study are the guided inquiry LKS which is seen from the second level of effective education which is almost the same, namely 0.72 at the high school level and 0.73 at the high school vocational education level. Seen from the learning material, guided inquiry LKS is more effective on straight motion material, static fluid and vibration & sound waves with a high category. Judging from the dependent variable used, the effectiveness value with a high category is found in literacy skills, higher order thinking skills and student learning outcomes. This can be concluded that the inquiry LKS guided in physics learning is effectively used in the learning process.